2020
DOI: 10.3390/ijerph17061823
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Body Mass Index, Energy Intake, and Fluid Intake over 60 Months Premortem as Prognostic Factors in Frail Elderly: A Post-Death Longitudinal Study

Abstract: Survival prediction is considered difficult in elderly individuals with cognitive frailty or dementia that leads to death. The aim of this study was to verify temporal changes in body mass index (BMI), energy intake, and fluid intake measured continuously in frail elderly people as prognostic factors for death. We assessed 106 frail elderly individuals who received >2-year care at an elderly care facility and died at the facility. We analyzed temporal changes in BMI, energy intake, and fluid intake from a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…Other variables associated with frailty included BMI and haemoglobin level. Previous studies [ 32 , 33 ] have also found that people with lower BMI have higher risks of frailty, subsequently increasing the risk of death [ 34 ]. Low haemoglobin levels (anaemia) have also been associated with a higher risk of developing frailty [ 35 – 37 ], similar to the results of the current study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other variables associated with frailty included BMI and haemoglobin level. Previous studies [ 32 , 33 ] have also found that people with lower BMI have higher risks of frailty, subsequently increasing the risk of death [ 34 ]. Low haemoglobin levels (anaemia) have also been associated with a higher risk of developing frailty [ 35 – 37 ], similar to the results of the current study.…”
Section: Discussionmentioning
confidence: 99%
“…This study was approved by the Ethics Committees of Tokyo Medical and Dental University and Omihachiman Community Medical Center, and it was conducted in accordance with the ethical principles of the Declaration of Helsinki. All of the participants provided written informed consent (approval number M2018-021, [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46].…”
Section: Fundingmentioning
confidence: 99%
“…This study has four major limitations. First, BMI was used as an assessment of nutritional status because BMI is an easy and non-invasive indicator, and is readily available for significant clinical studies [ 1 , 2 , 4 , 5 , 25 ]. However, BMI is just one aspect of nutritional status and is influenced by various lifestyle factors such as physical activity, diet, and general health/disease status).…”
Section: Discussionmentioning
confidence: 99%
“…Individuals who are overweight and obese are at an increased risk for many diseases and health conditions, and there is a direct relationship between high body mass index (BMI) and all-cause mortality [ 1 , 2 , 3 ]. Conversely, undernutrition, as indicated by a low BMI, is also associated with an increased risk of all-cause mortality; this is of particular concern among frail older adults [ 4 , 5 ]. Undernutrition has a varied etiology, of which impaired masticatory ability is the primary focus in the field of dentistry.…”
Section: Introductionmentioning
confidence: 99%
“…Cheng and colleagues [ 5 ] used data from the medical records of 305 patients with advanced cancer attending the Emergency Departments of three hospitals in Taiwan, showing the strong predictive power of a simple index, named the Shock index (pulse rate/systolic blood pressure), in predicting 60-day survival rate. Kawakami and Hamano [ 6 ] analyzed data from 106 residents with moderate-to-severe impairment of activities of daily living (ADL) and cognitive frailty in a nursing home in Japan, showing that change in body mass index, energy intake, and fluid intake were prognostic factors for death. Both studies highlighted the importance of the use of the simple evaluation tools based on routine measurements in identifying patients near end-of-life so that physicians in these settings can initiate advanced care planning discussions with identified patients and their families in a timely manner.…”
Section: Included Workmentioning
confidence: 99%